Transnasal endoscopic resection of symptomatic ecchordosis physaliphora. (29th October 2013) - Bolzoni‐Villaret, Andrea; Stefini, Roberto; Fontanella, Marco; Bottazzoli, Marco; Turri Zanoni, Mario; Pistochini, Andrea; Castelnuovo, Paolo; Nicolai, Piero
<x xml:space="preserve">Abstract</x> Laryngoscope, 124:1325–1328, 2014